PENGARUH KEPERCAYAAN DAN KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN AVIE WEDDING ORGANIZER DI KOTA MALANG - Mafaza Himma, Fishna (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
The Wedding Organizer service business is one form of business that aims to help the community when they want to do a wedding. This condition is used by wedding organizer manufacturers as a big opportunity, giving rise to a lot of wedding organizer business competition that requires wedding organizer manufacturers to pay attention to factors that are considered by consumers. Trust and service quality are important aspects that can affect customer loyalty. Avie Wedding Organizer is a service company that always tries to provide the best for consumers. This study aims to determine the effect of trust and service quality on customer loyalty Avie Wedding Organizer in Mmalang City. This research is a quantitative research with two independent variables, namely Trust (X1) and Service Quality (X2) and one dependent variable, namely Customer Loyalty (Y). This research uses data collection method by distributing questionnaires to 80 respondents. The sampling technique used is purposive sampling. The data analysis technique used is multiple linear regression, coefficient of determination, hypothesis testing. The results of this study indicate that the variables of trust and service quality have a significant effect simultaneously on customer loyalty. based on the trust variable, it is known that the Avie Wedding Organizer provides trust that makes customers feel satisfied, while the service quality variable provides comfortable service to customers, and with the appropriate trust and service quality, customers will use the Avie Wedding Organizer services repeatedly. Based on the results of this study, it was concluded that Avie Wedding Organizer in Malang City can increase trust and service quality, so that customers become satisfied with the services provided